Applying Critical Linguistics to Literary Texts: Transitivity in Charles G.D. Roberts' “Do Seek Their Meat From God” - Lillian, Donna L. (Papers from the Annual Meetings of the Atlantic Provinces Linguistic Association (PAMAPLA) / ACTES DES COLLOQUES ANNUELS DE L’ASSOCIATION DE LINGUISTIQUE DES PROVINCES ATLANTIQUES (ACAALPA)., 2001)
Critical linguistics is perhaps most prominently employed in analyses of non-fiction texts such as newspaper accounts, political speeches, and political propaganda, but the insights of this approach can also be profitably employed in the analysis of the traditional literary genres. In the present paper, I utilize the methodology of critical linguistics, in particular the notion of transitivity, to analyze a short story by Canadian author Charles G. D. Roberts. Although below the level of consciousness of most readers, the variations in the level of transitivity of the actions attributed to the different characters contribute significantly to the ‘message’ of the story.